KEPASTIAN HUKUM PANDEMI COVID 19 SEBAGAI PENENTUAN KEADAAN KAHAR DI DALAM PERJANJIAN PEMBIAYAAN MULTIGUNA - Hendra Dinata; Ismail Ismail; Puguh Aji Hari Setiawan (LPPM Institut Pendidikan Nusantara Global, 2023)
Whereas in civil law there is a force majeure in the event of a failure to fulfill performance in an agreement. The President issued Presidential Decree Number 12 of 2020 concerning Designation of the Non-Natural Disaster of the Spread of CoronaVirus Disease 2019 (COVID-19) as a national disaster. One of the impacts of the Covid-19 outbreak is that economic growth has decreased, including in terms of agreements. Therefore, this study aims to examine the arrangements and legal certainty of multipurpose financing agreements in force majeure, in which parties who cannot fulfill their performance obligations as a result of being affected by Covid-19 cannot be immediately declared as default due to an element of intent. As a result of the Covid-19 pandemic, disputes arose between debtors and creditors, using the theory of legal agreements and the theory of legal certainty.The method used in this writer is normative juridical research carried out as an effort to obtain the necessary data in connection with the problem. The data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Besides that, primary data and secondary legal materials are also used. Data analysis was carried out using a qualitative juridical analysis method.The research results obtained, that multipurpose financing agreements in force majeure in this case the Covid-19 pandemic have an impact on debtors not carrying out achievements or defaults not caused by intentional or negligent factors, but because of circumstances that occur beyond expectations and debtor capabilities, legal remedies to resolve default disputes by debtors during the Covid-19 pandemic, dispute resolution outside the court is by negotiating with the parties